Newly isolated Bacillus sp. G51 from Patagonian wool produces an enzyme combination suitable for felt-resist treatments of organic wool - Iglesias, Martín Sebastián (2017)
Bacteria from Patagonian Merino wool were isolated to assess their wool-keratinolytic activity and potential for felt-resist treatments. Strains from Bacillus, Exiguobacterium, Deinococcus, and Micrococcus produced wool-degrading enzymes. Bacillus sp. G51 showed the highest wool-keratinolytic activity. LC-MS/MS analysis revealed that G51 secreted two serine proteases belonging to the peptidase family S8 (MEROPS) and a metalloprotease associated with Bacillolysin, along with other enzymes (γ-glutamyltranspeptidase and dihydrolipoyl dehydrogenases) that could be involved in reduction of keratin disulfide bonds. Optimum pH and temperature of G51 proteolytic activity were 9 and 60 °C, respectively. More than 80% of activity was retained in H2O2, Triton X-100, Tween 20, Lipocol OXO650, Teridol B, and β-mercaptoethanol. Treatment of wool top with G51 enzyme extract caused a decrease in wool felting tendency without significant weight loss (<1.5%). Sparse work has so far been performed to investigate suitable keratinases for the organic wool sector. This eco-friendly treatment based on a new enzyme combination produced by a wild bacterium has potential for meeting the demands of organic wool processing which bans the use of hazardous chemicals and genetic engineering.